"After 9/11 everything changed": Re-formations of state violence in everyday life on the US–Mexico border. (March 2013) - Correa, Jennifer G
After 11 September 2001, the state declared a War on Terror, repositioning "Arab-Middle-Eastern-Muslims" as threats to national security, and later broadening its scope to include immigrants crossing the US–Mexico border. This discursive shift propelled the passage of the Secure Fence Act of 2006 (approximately 700 mile barrier between the United States and Mexico) to curtail unauthorized immigration and international terrorism. This article focuses on the effects of militarization on Cameron County, Texas residents living in the Texas Lower Rio Grande Valley as they contend with an assemblage of security apparatuses in their communities. The objective is to move beyond institutional understandings of "the state" and focus on the micropolitics of sovereignty or what I call the state as lived experience . Using ethnographic methods, three manifestations of the state— dispossessor, irrational legal–political force, and arbiter of knowledge —emerge in the everyday lives of residents.